Sludge worms species (Oligochaeta: Naididae: Tubificinae) From Different Aquatic Habitat in Baghdad / Iraq (Baghdad Science Journal, 2013)
The present investigation is concerned primarily with sorting and identification of subfamily Tubificinae from River Tigris and some water surface in Baghdad /Iraq . For this purpose six study sites were chosen, including a Al- Kadhemyia drainage canal, North Baghdad; three sites on the shore of River Tigris; in addition to site in Al-Jaish canal , East Baghdad, finally the sixth site was from pond in Al-Zawra'a park , within the center of Baghdad .These sites were characterized by sediment rang from clay, silty-clay to silty with a percentage of organic matter ranged between 0.7% - 9.9% . According to water temperature, salinity and pH values, they were nearly identical in all study sites, the water temperature was ranged through the study periodbetween 12.5 – 300 C , while electrical conductivity and salinity values were ranged beteen 733.5-1227.5 ?s ,which equivalent to 0.469-0.787 ‰ salinity. All sites were slightly alkaline ,so the pH values were ranged between 7.5-8.1.3628 individuals were sorted from 24 samples collected from different study sites.. Twelve species were identified belonging to seven genera, including , Limnodrilus hoffmeisteri, L. claparedeianus, .L. profundicola, . L.udekemianus , L. silvani, Tubifex tubifex, Branchiura sowerbyi, Potamothrix.2013 )2( ???? ????? ?????? ???? 10982bavaricus, , P. hammoniensis, Psammoryctide moravicus, Monopylephorus irroratus, and Rhyacodrilus coccineus.The result revealed that Al-Jaish canal and Tigris River / al-Sarafyia were considered as the richest sites according to the number of species recorded, where 8 species were recorded in each of them, but Al-Jaish canal had higher individual number of 1346 individuals , followed by Al-Kadhemyia drainage canal recorded only three species with high total individual number of 606 individual. The lowest total individual number was recorded in Tigris River / Al- Zaafaranyia of 326 individual.L. hoffmeisteri, records higher individuals number of 1870 individual , followed by B. sowerbyi which records 946 individual. Both species recorded highest percentage occurance of 100% followed by 79.16% recorded by L. profundicola.High densities of Tubificinae were recorded during all study period. The highest density was during March-April, reached between 2109 -534.9 ind/m2 in Tigris River sites , 7270.5 ind/m2 in Al-Jaish canal and 2419.8 ind/m2 in Al-Zawra'a pond. The .results of relative abundance revealed that L. hoffmeisteri was the dominant species in site Tigris River/Al- Jaderyia, and abundant in other study sites. B. sowerbyi was abundant in all study sites, while other species were recorded between few to rare species except L. udekemianus which was abundant in site Al-Jaish canal, and T. tubifex in site Tigris River / Al- Zaafaranyia.